2014
DOI: 10.1021/la5020362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Potential on Extracellular Matrix Protein Adsorption

Abstract: Extracellular matrix (ECM) proteins, such as fibronectin, laminin, and collagen IV, play important roles in many cellular behaviors, including cell adhesion and spreading. Understanding their adsorption behavior on surfaces with different natures is helpful for studying the cellular responses to environments. By tailoring the chemical composition in binary acidic (anionic) and basic (cationic) functionalized self-assembled monolayer (SAM)-modified gold substrates, variable surface potentials can be generated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 42 publications
3
68
2
Order By: Relevance
“…Previous work by You et al shows that the amount of Fn adsorbed increased with increasing surface charge density of self-assembled monolayers within a range of −28 to −121 mV, and decreased at even higher surface charge density. Their work implies that, within such range of surface charge density, microscopic polarization rather than macroscopic electrostatic repulsion plays a dominant role in Fn adsorption [56]. Although the polarization effect is weaker on micro-rough facets due to lower surface charge density, lower electrostatic repulsion combined with higher probability of mechanical entrapment of Fn molecules within surface features can lead to higher Fn adsorption onto micro-rough facets than onto their nano-rough counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by You et al shows that the amount of Fn adsorbed increased with increasing surface charge density of self-assembled monolayers within a range of −28 to −121 mV, and decreased at even higher surface charge density. Their work implies that, within such range of surface charge density, microscopic polarization rather than macroscopic electrostatic repulsion plays a dominant role in Fn adsorption [56]. Although the polarization effect is weaker on micro-rough facets due to lower surface charge density, lower electrostatic repulsion combined with higher probability of mechanical entrapment of Fn molecules within surface features can lead to higher Fn adsorption onto micro-rough facets than onto their nano-rough counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…[37, 38, 42, 43] In previous work, it has been observed that proteins in culture adsorb at a faster rate than cell attachment, and dictate cell-surface interactions. [38, 44] Specifically the adsorption of proteins to hydrophobic/hydrophilic and charged surfaces has shown that specific extracellular matrix proteins bind in a surface dependent manner, with variability in their tertiary structure, resulting in variation in available cellular attachment domains.…”
Section: Discussionmentioning
confidence: 99%
“…[38, 44] Specifically the adsorption of proteins to hydrophobic/hydrophilic and charged surfaces has shown that specific extracellular matrix proteins bind in a surface dependent manner, with variability in their tertiary structure, resulting in variation in available cellular attachment domains. [3739, 43, 45]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding their adsorption behavior on surfaces with different natures is helpful for studying the cellular responses to environments. [11] Various polymers, including natural, synthetic and natural/synthetic hybrid polymers, have been used to make hydrogels via chemical or physical crosslinking. Recently, bioactive synthetic hydrogels have emerged as promising scaffolds because they can provide molecularly tailored biofunctions and adjustable mechanical properties, as well as an extracellular matrix-like microenvironment for cell growth and tissue formation.…”
Section: Introductionmentioning
confidence: 99%